Contemplative practices and their impact on achievement motivation among primary school mathematics teachers in the Alqassim region - Alturki, Abdullah Mansour; Alnosaian, Abdurahman Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify contemplative practices and their impact on achievement motivation among primary school mathematics teachers in the Al-Qassim region. To achieve this, a qualitative research approach was used. They have enthusiasm, willingness to participate in the study, and a desire to develop their teaching performance to obtain information, and the study tool was the use of the interview, and the results of the study resulted in the teachers ’contemplative practices being practiced in a moderate degree and affected by the degree of their confidence in their sufficiency related to achieving the learning objectives, and their beliefs and values that they carry towards Teaching, and a direct reflection on achievement motivation, as the results showed that teachers used contemplative practices in education and diversified in using strategies that help students develop their creative thinking, and the results showed that there is a positive relationship between contemplative practices and achievement motivation among mathematics teachers, as the results showed. It is one of the most prominent means of promoting contemplative practices to positively affect DAF Realization of achievement, application of educational games, taking into account individual differences, use of problem-solving strategy and the development of higher levels of thinking. The researcher recommends the necessity of enhancing the reflective teaching skills of mathematics teachers by adopting procedural research, training peers, activating reciprocal participation among colleagues of the specialization, in addition to developing self-evaluation skills among teachers, and working on directing mathematics teachers towards employing contemplative teaching, and developing the capabilities of mathematics supervisors on Exercise this role.